2023
DOI: 10.3390/separations10010026
|View full text |Cite
|
Sign up to set email alerts
|

Paper Spray Tandem Mass Spectrometry for Assessing Oleic, Linoleic and Linolenic Acid Content in Edible Vegetable Oils

Abstract: Oleic, linoleic and linolenic acids exert several beneficial effects on human health, some of which are also certified by recent European and U.S. regulations. The goal of the presented work was to develop an innovative methodology to evaluate their content in edible vegetable oils, in order to increase the value of oils from a nutraceutical perspective. The protocol is based on the use of paper spray ionization coupled with tandem mass spectrometry experiments, which allowed the recording of data very quickly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Paper spray mass spectrometry has found widespread application in many areas; in food analysis, for example, it has already been used to carry out molecular screening and quantification of several nutraceutical compounds for assessing products quality and authenticity. [26][27][28][29][30][31][32][33] Furthermore, it has been demonstrated that paper spray ionization may provide comprehensive MS profiles by detecting a large number of molecules, comparable to those achieved by direct infusion analysis. With respect to other commonly used ambient sources, PS-MS seems to be excellent for the analysis of polar compounds, such as organic acids and phenols in food matrices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paper spray mass spectrometry has found widespread application in many areas; in food analysis, for example, it has already been used to carry out molecular screening and quantification of several nutraceutical compounds for assessing products quality and authenticity. [26][27][28][29][30][31][32][33] Furthermore, it has been demonstrated that paper spray ionization may provide comprehensive MS profiles by detecting a large number of molecules, comparable to those achieved by direct infusion analysis. With respect to other commonly used ambient sources, PS-MS seems to be excellent for the analysis of polar compounds, such as organic acids and phenols in food matrices.…”
Section: Introductionmentioning
confidence: 99%
“…These latter are transported and released into an ionized spray by the simultaneous application of a polar solvent and a high voltage to the paper. Paper spray mass spectrometry has found widespread application in many areas; in food analysis, for example, it has already been used to carry out molecular screening and quantification of several nutraceutical compounds for assessing products quality and authenticity 26–33 . Furthermore, it has been demonstrated that paper spray ionization may provide comprehensive MS profiles by detecting a large number of molecules, comparable to those achieved by direct infusion analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The great variety of edible mushrooms found worldwide and their consistent production of fatty acids, regardless of the geographic source, make them an important source of essential fatty acids within a healthy human diet. Their lipid profiles include essential fatty acids such as the linoleic acids (LAs), oleic acids (OAs), and linolenic acids, which act against cardiovascular diseases [36]. LA is a PUFA that has anti-tumor activity against cytotoxic T lymphocytes (CD8+T) cells in vitro and in vivo and can be considered an enhancer of adoptive T cell therapy in cancer therapy [37].…”
Section: Introductionmentioning
confidence: 99%